2014
DOI: 10.1136/bcr-2013-201268
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of geographic tongue with topical tacrolimus

Abstract: Geographic tongue is an inflammatory condition of the dorsal surface and lateral border of the tongue, which may be asymptomatic. This article presents a case of geographic tongue in a 6-year-old child. Successful management was achieved with topical application of 0.1% tacrolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Clinically, GT is characterized by an erythematous, atrophic area circumscribed by a yellowish‐white line. The lesions often change their location and shape over a span of a few minutes and primarily affect the dorsum of the tongue . Kuffer demonstrated that GT lesions may also exist without delineation by a white border and proposed a clinical classification (the first described) as follows: typical, migratory lesions with a white border; atypical, nonmigratory lesions without a white border; and mixed, a combination of the two forms in a single patient .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, GT is characterized by an erythematous, atrophic area circumscribed by a yellowish‐white line. The lesions often change their location and shape over a span of a few minutes and primarily affect the dorsum of the tongue . Kuffer demonstrated that GT lesions may also exist without delineation by a white border and proposed a clinical classification (the first described) as follows: typical, migratory lesions with a white border; atypical, nonmigratory lesions without a white border; and mixed, a combination of the two forms in a single patient .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of GT is based on the clinical features of the lesion, and histopathological confirmation is rarely performed, making it difficult to study its pathogenesis . Treatment is indicated only in symptomatic cases and often includes corticosteroids . Some authors suggest that GT may represent an early oral manifestation of psoriasis and have described the relationship between GT and the severity of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Benign migratory glossitis is a pathological condition referred to in literature as geographic tongue, annulus migrans, erythema migrans, benign wandering glossitis, exfoliatio areata linguae, or transitory benign plaque of the tongue [1][2][3]. It is an asymptomatic inflammatory disorder of unknown etiology considered as a normal variant rather than an injury.…”
Section: Introductionmentioning
confidence: 99%
“…Plus récemment, deux cas de LG symptomatique traité par tacrolimus local ont été décrits [2][3][4], dont l'un chez un enfant de 6 ans [4]. L'objectif de cette étude rétrospective était d'évaluer l'efficacité du tacrolimus dans le traitement des langues géo-graphiques algiques sur une série de dix patients.…”
Section: Introductionunclassified